Sustainability Improvement Aspects related to Fashion Ecoprint - Kuhnen, Gabriela (2023)
This article presents a study on the practices of ateliers, workshops and productive groups of natural dyeing and fashion ecoprint.. These small businesses work with natural inputs and non-industrial processes, however, improving sustainability requires, in addition to brand communication, a profound ecological approach with systemic, coherent and efficient technical and managerial procedures that consider an expanded view of the production chain. The content of this article is part of a broader research, but the clipping presented here stems from a descriptive study, with exploratory, theoretical bibliographic and documental stages, whose results are presented with indications or eco-conscious principles related to fibers, fabrics and plants. This is because, in addition to including internal actions, sustainability, in this context, requires care in the external environment, which includes suppliers of textile supports. Likewise, internally, the practices carried out in ateliers and workshops require decisions of lesser or greater environmental impact that must be considered throughout the process.